Training programme in micro-enterprises for women entrepreneurs in marketing and industrial processing of foods - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
In order to see the training programme in a wider context, this paper sums up some of the well known facts regarding women in industry especially women in rural small scale industrial enterpreses (RSIE). This includes the definition of specific constraints facing women in this sector, and general considerations which should be taken into account in order to facilitate their integration and participation. In addition, the paper deals with UNIDO's mandate for the integration of women in industrial development and the relationship between rural development and the industry sector. More specifically, it gives a brief overview of activities undertaken by UNIDO having an impact on rural development as such and activities for rural women in particular. Based upon this background information, the paper finally gives a description of the UNIDO Training Programme for Women Entrepreneurs in the Food Processing Industry, the rationale behing the concept, its contents and structure, and the adaptation and dissemination of the programme to other parts of the world.